Impact of radiotherapy on the prognosis in uterine cervical adenocarcinoma: a meta-analysis and retrospective cohort study - Zhang, Keyi; Ji, Jianan; Yang, Jing; Zhou, Shulin; Qiu, Jiangnan; Luo, Chengyan (Frontiers in Oncology, 2025)
IntroductionThe treatment of uterine cervical adenocarcinoma (UAC) has always been a clinical challenge. The study investigated the effect of radiotherapy (RT) on survival outcomes and tumor recurrence in patients with UAC and further explored potential candidates who may benefit from RT.MethodsWe systematically searched the literature on the effects of RT on disease-free survival (DFS) and overall survival (OS) for UAC and performed a meta-analysis. The impact of RT on the cancer-specific survival (CSS) and DFS were retrospectively analyzed with the UAC cases from the Surveillance, Epidemiology, and End Results (SEER) database and at our center. A total of 4382 patients from the SEER database after propensity score matching and 315 cases at our center were retrieved, respectively. Univariate and multivariate Cox regression analysis were employed to investigate the effect of RT on the prognosis. Subgroup analysis was conducted to identify populations that may benefit from RT.ResultsThe meta-analysis revealed that RT didn’t improve DFS (OR: 0.72, 95% CI 0.34 - 1.52) and OS (OR: 0.44, 95% CI 0.18 - 1.07), in FIGO stage IB-IIA patients with UAC. The retrospective study found that RT improved CSS (HR: 0.87, 95% CI 0.78 - 0.9), but not DFS (HR: 2.62, 95% CI 0.96 - 6.8). Those with stage pT2-4, pN1, pM1, primary tumor size > 39 mm, grade III-IV, or unresected primary tumors had superior CSS when treated with RT than those without RT. In terms of DFS, the cases staged as pT1-2, pN0, pM0, with tumor > 19 mm, graded III-IV, resection of primary tumor, no parametrial involvement, and with or without lymph-vascular stromal invasion had worse outcomes after receiving RT.ConclusionThe UAC patients with more advanced, larger primary tumors, higher histological grade, and unresected primary tumors are likely to benefit from RT, which need to be substantiated by prospective studies.